2016
DOI: 10.1007/s11356-016-8312-7
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of Polygonum perfoliatum L. following exposure to elevated manganese concentrations

Abstract: Polygonum perfoliatum L. is a Mn-tolerant plant as considered having the potential to revegetate in manganese mine wasteland. The glasshouse experiments were carried out to evaluate its tolerance and physiological response in different Mn concentrations (5, 500, 1000, 2000, 5000, and 10,000 μmol L). Absorption bands of P. perfoliatum differed greatly in lipids, proteins, and carbohydrates. With elevated levels of Mn (5-2000 μmol L), absorbance changed little, which demonstrated that lower Mn concentrations had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…These values are close to those in a previous study 4 , in which the BCF of B obtained for L. minor and L. gibba was ~350 and ~425 respectively, at 2 mg B/L. Two criteria, the BCF and the translocation factor (TF, shoot or leaf concentration/root concentration), have been used to identify the hyperaccumulation of an element 35 , 36 . When both BCF and TF exceed 1.0, hyperaccumulation is thought to occur 37 .…”
Section: Resultssupporting
confidence: 85%
“…These values are close to those in a previous study 4 , in which the BCF of B obtained for L. minor and L. gibba was ~350 and ~425 respectively, at 2 mg B/L. Two criteria, the BCF and the translocation factor (TF, shoot or leaf concentration/root concentration), have been used to identify the hyperaccumulation of an element 35 , 36 . When both BCF and TF exceed 1.0, hyperaccumulation is thought to occur 37 .…”
Section: Resultssupporting
confidence: 85%
“…In the control sample, the IR absorption band was observed at 3395 cm −1 which indicated the symmetric stretch of the aliphatic primary amine group (–NH) which confirmed the presence of proteins. The peak that emerged at 2920 cm −1 is related to asymmetric vibration of C-H bonds of an aliphatic group (=CH 2 ) of the fatty acid backbone ( Driver et al, 2015 ; Xue et al, 2018 ). The peaks between 2000–2500 cm −1 are referred as a triple bond region.…”
Section: Discussionmentioning
confidence: 99%
“…The observed changes may be related to the substrate characteristics, where the soluble cations, predominantly Ca and Mg, may have been exchanged with non-exchangeable and buffered soluble K as well as by organic acids produced by plant roots into the rhizosphere [63]. Moreover, plants have developed several means of metal detoxification, such as separation, chelation, avoidance and exclusion, which involve LMWOAs via extra-and/or intracellular mechanisms [64,65]. Many studies are in accordance with our results and have reported that plants are able to accumulate significant amounts of heavy metals such as Cd, Cu, Pb and Zn, transfer them to the aerial parts and store them in vacuoles as complexes with citric and malic ligands [66].…”
Section: Physiological Responsementioning
confidence: 99%